Uninterrupted direct oral anticoagulants and vitamin K antagonists during ablation for atrial fibrillation: an updated meta-analysis. (25th November 2020) - Brockmeyer, M; Lin, Y; Parco, C; Karathanos, A; Krieger, T; Schulze, V; Heinen, Y; Bejinariu, A; Mueller, P; Makimoto, H; Kelm, M; Wolff, G
Abstract: Background: Uninterrupted anticoagulation during catheter ablation of atrial fibrillation (CAAF) became standard of care after positive results of trials investigating vitamin K antagonists (VKA). Previous studies and meta-analyses of uninterrupted direct oral anticoagulants (DOAC) vs. VKA have given controversial results. We thus aimed to elucidate the risks and benefits of uninterrupted DOAC vs. VKA during CAAF in an updated meta-analysis of randomized controlled trials (RCTs). Methods: Online databases were searched for RCTs comparing uninterrupted DOAC to VKA in patients undergoing CAAF until September 2019. Data from retrieved studies were analysed in a comprehensive meta-analysis. Primary safety outcome was major bleeding; primary efficacy outcome was stroke or transient ischemic attack (TIA). Secondary outcomes included a composite of major bleeding and stroke or TIA, minor bleeding, acute cerebral lesions on magnetic resonance imaging (ACL) and mortality. Results: Six eligible RCTs comprising 2, 369 patients were included. Pooled meta-analysis showed no significant differences in DOAC vs. VKA concerning the rates of major bleeding (2.2% vs. 3.8%; odds ratio (OR) 0.69, 95% confidence interval (CI) 0.30–1.56; p=0.37) and stroke or TIA (0.2% vs. 0.2%; OR 0.97, CI 0.20–4.72; p=0.97). There were no significant differences found in secondary outcomes (OR 0.73, p=0.49 for composite of major bleeding and stroke or TIA; OR 1.08, p=0.52 for minor bleeding; OR 1.12, p=0.59 for ACL; and OR=0.60, p=0.64 for all-cause mortality). Conclusion: Our meta-analysis suggests that uninterrupted periprocedural anticoagulation with DOAC or VKA is characterized by a similar risk/benefit ratio in patients undergoing CAAF with comparable rates of major bleeding and stroke. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical faculty of the Heinrich-Heine-University Düsseldorf, Germany